Amine functionalized tetraphenylethylene: a novel aggregation-induced emission based fluorescent chemodosimeter for nitrite and nitrate ions. Issue 40 (8th April 2015) - Chatterjee, Amrita; Khandare, Dipratn G.; Saini, Praveen; Chattopadhyay, Anjan; Majik, Mahesh S.; Banerjee, Mainak
Abstract : A novel AIE-based fluorescent probe for the detection of trace amounts of nitrite and nitrate ions in water has been developed, which spontaneously detects nitrites (or nitrates) by a fluorescence "turn-off" method. Abstract : A novel AIE-based fluorescent probe for the detection of trace amounts of nitrite and nitrate ions in water has been developed. The probe, a monoamine of tetraphenylethylene, spontaneously detects nitrites (or nitrates) by a fluorescence "turn-off" method via diazotization followed by formation of a non fluorescent TPE-azodye. The salient features of this method are high sensitivity and selectivity, cost effective synthesis, fast detection process and low detection limit.